Competing antiferromagnetism in a quasi-2D itinerant ferromagnet: Fe3GeTe2. (15th November 2016) - Yi, Jieyu; Zhuang, Houlong; Zou, Qiang; Wu, Zhiming; Cao, Guixin; Tang, Siwei; Calder, S A; Kent, P R C; Mandrus, David; Gai, Zheng
Abstract: Fe3 GeTe2 is known as an air-stable layered metal with itinerant ferromagnetism with a transition temperature of about 220 K. From our extensive dc and ac magnetic measurements, we have determined that the ferromagnetic layers of Fe3 GeTe2 actually order antiferromagnetically along the c -axis below 152 K. The antiferromagnetic state was further substantiated by theoretical calculation to be the ground state. A magnetic structure model was proposed to describe the antiferromagnetic ground state as well as competition between antiferromagnetic and ferromagnetic states. Fe3 GeTe2 shares many common features with pnictide superconductors and may be a promising system in which to search for unconventional superconductivity.